2019
DOI: 10.5693/djo.01.2019.02.005
|View full text |Cite
|
Sign up to set email alerts
|

The use of self-retained, cryopreserved amniotic membrane for the treatment of Sjögren syndrome: a case series

Abstract: Purpose-To determine whether signs and symptoms of ocular surface disease improve after placement of a self-retained, cryopreserved amniotic membrane (CAM) in patients with Sjögren syndrome (SS). Methods-The medical records of SS patients who received a self-retained CAM implant (Prokera or Prokera Slim; TissueTech Inc, Doral, FL) for the treatment of ocular surface disease between August 2012 and August 2016 at a single, large academic institution were reviewed retrospectively. Visual acuity, results of slit-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…166 Regarding AMT, Shafer et al evaluated the use of self-retained, cryopreserved AMT in six eyes of patients with refractory DED related to SS. 168 In all cases, staining of the conjunctiva and cornea improved, as well as referred symptoms. Unfortunately, signs and symptoms relapsed in 24.6 days (range 19 – 29 days).…”
Section: Management Of Dry Eye In Patients With Autoimmune Diseasesmentioning
confidence: 81%
“…166 Regarding AMT, Shafer et al evaluated the use of self-retained, cryopreserved AMT in six eyes of patients with refractory DED related to SS. 168 In all cases, staining of the conjunctiva and cornea improved, as well as referred symptoms. Unfortunately, signs and symptoms relapsed in 24.6 days (range 19 – 29 days).…”
Section: Management Of Dry Eye In Patients With Autoimmune Diseasesmentioning
confidence: 81%
“…Yi et al managed to prepare a contact lens-shaped AM using glutaraldehyde and dialdehyde starch as a cross-linking agent [39]. The literature reports the use of a self-retaining cryopreserved amniotic membrane (PROKERA ® Slim, Bio-Tissue, Miami, FL, USA) for the treatment of dry eye disease [40], corneal ulcers [41], Stevens-Johnson syndrome/toxic epidermal necrolysis [42], and Sjögren's syndrome [43]. Some authors reported the use of a symblepharon ring in order to fix the AM to the ocular surface in patients with chemical injuries or toxic epidermal necrosis/Stevens-Johnsons syndrome [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…[ 60 ] In cases that are refractory to standard therapies, the use of ProKera ® is beneficial in the improvement of symptoms and ocular surface staining in patients with SS. [ 62 ] Moreover, AMT can promote the healing of corneal melting and ulceration. [ 63 64 ] The inflammation in immune-related DED is more severe and progressive than nonimmune-related DED.…”
Section: Clinical Evidence Of Amniotic Membrane Transplantation In Sjogren's Syndromementioning
confidence: 99%